2010
DOI: 10.1002/pbc.22355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytarabine against Ewing sarcoma xenografts by the pediatric preclinical testing program

Abstract: Treatment with the nucleoside analog cytarabine has been shown to mimic changes in gene expression associated with down-regulation of the EWS-FLI1 oncogene in Ewing sarcoma cell lines, selectively inhibit their growth in vitro, and cause tumor regression in athymic nude mice. For this report cytarabine was studied in vitro against a panel of 23 pediatric cancer cell lines and in vivo against 6 Ewing sarcoma xenografts. Acute lymphoblastic leukemia cell lines were the most sensitive to cytarabine in vitro (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Conversely, cytarabine was shown to inhibit the therapeutic target in Ewing's sarcoma, with compelling preclinical activity both in vitro and in vivo , yet no activity was observed in a subsequent phase II trial . Despite the specificity of cytarabine toward EWS‐FLI1 , subsequent preclinical studies in an extended in vivo panel inferred a lack of activity in this cancer type . Although it has been suggested that more rigorous preclinical testing may have predicted this clinical outcome prior to trial initiation , there are no objective data to help guide preclinical researchers and trialists as to how much preclinical evidence is needed before a trial should be initiated, which preclinical studies best predict clinical success, or the translational relevance of current preclinical testing paradigms .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, cytarabine was shown to inhibit the therapeutic target in Ewing's sarcoma, with compelling preclinical activity both in vitro and in vivo , yet no activity was observed in a subsequent phase II trial . Despite the specificity of cytarabine toward EWS‐FLI1 , subsequent preclinical studies in an extended in vivo panel inferred a lack of activity in this cancer type . Although it has been suggested that more rigorous preclinical testing may have predicted this clinical outcome prior to trial initiation , there are no objective data to help guide preclinical researchers and trialists as to how much preclinical evidence is needed before a trial should be initiated, which preclinical studies best predict clinical success, or the translational relevance of current preclinical testing paradigms .…”
Section: Introductionmentioning
confidence: 99%
“…For example, an mTOR inhibitor, MLN0128, was more active in solid tumor lines than in leukemia . Of note, the greatest differential sensitivity of the leukemic cell line panel over the solid tumor panel was for cytosine arabinoside (cytarabine), a drug used extensively in the treatment of childhood ALL …”
Section: Discussionmentioning
confidence: 99%
“…[8] Of note, the greatest differential sensitivity of the leukemic cell line panel over the solid tumor panel was for cytosine arabinoside (cytarabine), a drug used extensively in the treatment of childhood ALL. [9] In vivo, NSC 750854 was tested at a dose of 5 mg/kg administered IP daily for 5 days with the cycle repeated at day 15. This dose was selected based upon prior toxicity testing, and it is in the range of doses used previously against adult cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…Cytarabine was found to be the most active agent tested in study 2, a result supporting its use in the patient. Interestingly, whilst cytarabine induces differentiation in RMS cell lines reducing in vivo tumorigencity [44], cytarabine has been found to be ineffective in both a Phase II clinical trial in patients with relapsed or refractory Ewing sarcoma [45], and by the Pediatric Preclinical Testing Program (PPTP) in sarcoma cell lines, including RMS and Ewing sarcoma PDX models [46]. Taken together, these results support the use of predictions based on gene expression of initial patient tumor harvest and propagated F0 PDX tumors, thus potentially minimizing the need to re-sample a patient's tumor following the development of resistance.…”
Section: Discussionmentioning
confidence: 99%